Augmented low-Dye tape alters foot mobility and neuromotor control of gait in individuals with and without exercise related leg pain - Franettovich, Melinda (BioMed Central, 2010)
BACKGROUND: Augmented low-Dye (ALD) tape is frequently used in the management of lower limb musculoskeletal pain and injury, yet our knowledge of its effect is incomplete, especially in regard to its neuromotor effects. METHODS: We measured electromyographic (EMG) activity of twelve lower limb muscles, three-dimensional kinematics of the ankle, knee, hip and pelvis, foot posture and foot mobility to determine the physiological effect of ALD tape. Fourteen females with exercise related leg pain and 14 matched asymptomatic females walked on a treadmill under three conditions: pre-tape, tape and post-tape. A series of repeated measure analysis of variance procedures were performed to investigate differences in EMG, kinematic, foot posture and mobility measurements. RESULTS: Application of ALD tape produced reductions in recruitment of tibialis anterior (7.3%) and tibialis posterior (6.9%). Large reductions in midfoot mobility (0.45 to 0.63 cm) and increases in arch height (0.58 cm), as well as moderate changes in ankle motion in the sagittal (2.0 to 5.3°) and transverse planes (4.0 to 4.3°) were observed. Reduced muscle activation (<3.0%) and increased motion (<1.7°) was observed at more proximal segments (knee, hip, pelvis) but were of smaller magnitude than at the foot and ankle. Changes in foot posture, foot mobility, ankle kinematics and leg muscle activity did not persist following the removal of ALD tape, but at more proximal segments small changes (<2.2°, <5.4% maximum) continued to be observed following the removal of tape. There were no differences between groups. CONCLUSIONS: This study provides evidence that ALD tape influences muscle recruitment, movement patterns, foot posture and foot mobility. These effects occur in individuals with and without pain, and are dissipated up the kinetic chain. ALD tape should be considered in the management of individuals where increased arch height, reduced foot mobility, reduced ankle abduction and plantar flexion or reduced activation of leg muscles is desired.